Body Dissatisfaction and Disordered Eating and the Moderating Role of Emotion Regulation Strategies - Khanna Roy, Anjalika (Université d'Ottawa | University of Ottawa, 2025)
The global prevalence of eating disorders is estimated to be 2.58 to 8.4% in females and 0.74 to 2.2% in males. Although clinical diagnoses of eating disorders are relatively low, symptoms of disordered eating are common. Body dissatisfaction is a key risk factor for the development and maintenance of disordered eating and eating disorders, but not all individuals with body dissatisfaction have disordered eating. This suggests that there are factors that moderate this relation. In this study, emotion regulation strategy types were examined as moderators of the relation between body dissatisfaction and disordered eating in a community sample of 361 young adults (62.9% women, 76.7% White). Participants completed measures of body dissatisfaction, disordered eating, and their propensity to use six common emotion regulation strategies to downregulate negative emotions (Distraction, Rumination, Reappraisal, Relaxation/Arousal Control, Expressive Engagement, and Expressive Suppression). Results indicated that Rumination had the strongest direct association with body dissatisfaction and disordered eating. Further, Rumination was the only statistically significant moderator of the relation between body dissatisfaction and disordered eating. At all levels of Rumination, body dissatisfaction had a positive relation to disordered eating; this relation was significantly stronger as Rumination use was higher. Results suggest that Rumination may be a default emotion regulation strategy because it is a less effortful strategy, or due to neurocognitive vulnerabilities in individuals particularly susceptible to developing disordered eating when experiencing body dissatisfaction. Clinical implications are presented; notably, these results speak to the importance of psychoeducational training for effective emotion regulation, and interventions for body dissatisfaction and disordered eating that target cognitive styles, particularly the tendency for rumination.
Keywords: body dissatisfaction; disordered eating; emotion regulation; rumination